Clinical Characteristics of Rotavirus Gastroenteritis in Children in a Medical Center - Su-Tin Yang; Lung-Huang Lin; Hsiu-Mei Wu (Elsevier, 2010)
Rotavirus is one of the major causes of severe gastroenteritis in infants and young children worldwide. Methods: We retrospectively analyzed the demographic and clinical profiles of rotavirus infection among children hospitalized in the Cathay General Hospital, Taiwan from May 2004 to April 2007. Children under 15 years of age with gastroenteritis were enrolled in the study and had stool specimens tested for the presence of rotavirus. Results: There were 238 participating patients, most of whom were aged 3-5 years (44%). The most common symptom was diarrhea (98.7%), and the peak month was May (20.4%). All patients were discharged alive with no complications. Conclusion: Gastroenteritis due to rotavirus infection was found in older children between 6 and 12 years of age, as well as in hospitalized children between 3 and 5 years of age. Most cases occurred in the spring.